Investigate of the Energy Gap, Ionic Charge and Infrared Spectra (IR) Of Ge Nanocrystals (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Density functional theory (DFT) has been used in this work at the B3LYP level with (6-31G**) basis set to find out Energy Gap, Ionic Charge and Infrared Spectra (IR) of Ge  Nanocrystals for crystal  8, 16 , 54 , 64 and 128 atoms, the study shows that the energy gap decrease with increasing of the number of atoms in crystal which have the same lattice constant approximately .       While the atomic charge is studied for two states,  the 8 and 64 atoms oxygenated surfaces, the results show that there is a gradient of net charge from the oxygen atoms on the surface toward the Ge atoms at the center of each crystal,         According to Infrared spectra there are two types of stretching vibration, symmetric and asymmetric, the symmetric stretching happens when the  bonds of the same atoms vibrate in the same phase which appear as peak  point, and the asymmetric stretching happens when the bonds vibrate in different phases which appear as bottom point.